2013
DOI: 10.1309/ajcpakydo56nkmyz
|View full text |Cite
|
Sign up to set email alerts
|

The Role of S100-Positive Dendritic Cells in the Prognosis of Papillary Thyroid Carcinoma

Abstract: Dendritic cells are potent antigen-presenting cells, common in inflammatory processes. We sought to investigate dendritic cell expression in papillary thyroid carcinoma and the relationship of dendritic cell density with the extent of thyroiditis and prognosis. Specimens from 69 consecutive patients with papillary thyroid carcinoma were immunohistochemically stained for the S100 protein, and the number of positive dendritic cells was counted. Cells were sparse in normal thyroid tissue and common in areas of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
(29 reference statements)
5
34
0
Order By: Relevance
“…The recently published study analysing retrospectively thyroid specimens of 69 classical-type PTC patients revealed that S-100 + DC density, both in the tumoural tissue and areas of concomitant thyroiditis, was associated with the intensity of lymphocytic thyroiditis. Moreover, short-term disease-free survival correlated positively with the thyroiditis grade but not with the number of infiltrating DCs [99]. This observation seems to be very interesting in the light of earlier reports, showing distinctive for PTC phenotypes of infiltrating DCs including expression pattern of chemokines receptors and adhesion molecules [68,86], as well as low expression of costimulatory molecules such as CD86 [69,89,90].…”
Section: Thyroid Cancersupporting
confidence: 59%
“…The recently published study analysing retrospectively thyroid specimens of 69 classical-type PTC patients revealed that S-100 + DC density, both in the tumoural tissue and areas of concomitant thyroiditis, was associated with the intensity of lymphocytic thyroiditis. Moreover, short-term disease-free survival correlated positively with the thyroiditis grade but not with the number of infiltrating DCs [99]. This observation seems to be very interesting in the light of earlier reports, showing distinctive for PTC phenotypes of infiltrating DCs including expression pattern of chemokines receptors and adhesion molecules [68,86], as well as low expression of costimulatory molecules such as CD86 [69,89,90].…”
Section: Thyroid Cancersupporting
confidence: 59%
“…72 S100 C (mature and immature), CD1a C (immature), and CD83 C (mature) DCs are increased in human PTC compared to normal thyroid tissue. 73 CM obtained from primary cultures of PTC induced chemotaxis of peripheral blood monocytederived DCs. Hepatocyte Growth Factor (HGF) enhanced this chemotactic activity through the engagement of the receptor Met on TC cells.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 98%
“…Anania et al found that in papillary thyroid cancer an over-expression of S100A11 may contribute to the malignant phenotype [37], moreover, the role of S100-positive dendritic cells in this context has been recently discussed [38]. In laryngeal cancer S100A11 gene was over-expressed both on mRNA and protein level and its expression was associated with a migratory capacity [39].…”
Section: Discussionmentioning
confidence: 99%